Epidemiology of hypertension among Bangladeshi adults using the 2017 ACC/AHA Hypertension Clinical Practice Guidelines and Joint National Committee 7 Guidelines. (October 2018) - Islam, Jessica; Zaman, M.; Haq, Syed; Ahmed, Shamim; Al- Quadir, Zahid
Abstract In 2017, the American College of Cardiology (ACC) and American Heart Association (AHA) released updated guidelines on the definition of hypertension, and blood pressure thresholds for initiation of antihypertensive medication. Our objective was to assess the change in prevalence of hypertension, risk factors, and identify populations recommended for treatment among Bangladeshi adults, based on the 2017 ACC/AHA guidelines. Data for this analysis were collected from a population-based nationally representative sample of 1843 Bangladeshi adults, aged ≥18 years in 2015. Hypertension was defined based on two definitions: the JNC 7 guidelines (SBP ≥ 140 or DBP ≥ 90 mmHg), and the 2017 ACC/AHA guidelines (SBP ≥ 130 mmHg, or DBP ≥ 80 mmHg), or a self-reported diagnosis of hypertension. Based on the 2017 ACC/AHA guidelines, the prevalence of hypertension was 40.7% (95% CI: 38.5–43.0). The prevalence of JNC 7 definition of hypertension was 17.9% (95% CI: 16.2–19.7), indicating a 22.8% increase in prevalence. Based on both definitions, urban residents, older adults, adults with low physical activity, obese, abdominally obese, and diabetic adults were more likely to have hypertension. Based on current JNC 7 guidelines, only half of hypertensive adults were aware of having hypertension. Among those aware of their condition, 75% were taking medication based on self-report. Using the 2017 ACC/AHA guidelines, the prevalence of hypertension will more than double in Bangladesh. Newly diagnosed hypertensive adults will be considered high-risk for cardiovascular disease leading to a larger burden on Bangladesh's health system. However, implementation of the ACC/AHA guidelines may improve prevention efforts where lifestyle changes are appropriate.